2014
DOI: 10.1007/s00221-014-3888-y
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphene-guided transcranial magnetic stimulation of occipital but not parietal cortex suppresses stimulus visibility

Abstract: Transcranial magnetic stimulation (TMS) applied over the occipital lobe approximately 100 ms after the onset of a stimulus decreases its visibility if it appears in the location of the phosphene. Because phosphenes can also be elicited by stimulation of the parietal regions, we asked if the same procedure that is used to reduce visibility of stimuli with occipital TMS will lead to decreased stimulus visibility when TMS is applied to parietal regions. TMS was randomly applied at 0 to 130 ms after the onset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Although the perception of phosphenes is somewhat subjective, in recent years several studies on the visual cortex in healthy subjects and in patients, have used the intensity threshold at which phosphenes are elicited as a specific index of visual cortex excitability (e.g. [3,13,22,27,31,51,52,56]). The exact generation of phosphene perception is still under discussion, results suggest that PTs are not functionally analogous to motor-evoked potentials following TMS over M1 but more to conscious perception of visual stimuli, nevertheless occurring within an earlier time window [52].…”
Section: Discussionmentioning
confidence: 99%
“…Although the perception of phosphenes is somewhat subjective, in recent years several studies on the visual cortex in healthy subjects and in patients, have used the intensity threshold at which phosphenes are elicited as a specific index of visual cortex excitability (e.g. [3,13,22,27,31,51,52,56]). The exact generation of phosphene perception is still under discussion, results suggest that PTs are not functionally analogous to motor-evoked potentials following TMS over M1 but more to conscious perception of visual stimuli, nevertheless occurring within an earlier time window [52].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of phosphene reports revealed that subjects perceived a greater proportion of phosphenes with P3 stimulation than control site stimulation (P3 TMS: M= 55.7%, SD=19.1%; control site TMS: M=33.5%, SD=34.94%; t(9)=2.61, p=.028), consistent with greater activation of PPC with P3 stimulation than control site stimulation (Bagattini et al, 2015; Fried et al, 2011; Marzi et al, 2009; Mazzi et al, 2014; Tapia et al, 2014). However, it should be noted that the relatively high rate of phosphene reports associated with control site stimulation may indicate some spread of activation to left PPC during control site TMS.…”
Section: Resultsmentioning
confidence: 68%
“…Stimulation over this scalp location corresponds to BA 7/39/40 (Herwig et al 2003; Okamoto et al, 2004). We verified that coil position induced suprathreshold stimulation of PPC by ensuring that TMS to this location elicited a phosphene percept (Bagattini et al, 2015; Fried et al, 2011; Marzi et al, 2009; Mazzi et al, 2014; Tapia et al, 2014). We selected a stimulation site that elicited parietal phosphenes so that stimulation intensity could be set according to this phosphene threshold to ensure suprathreshold stimulation of PPC.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…And while one recent study did not obtain consistent visual suppression by TMS pulses over these parietal regions (Tapia et al, 2014), Koivisto et al (2014) did report evidence for parietal (inferior parietal sulcus) TMS masking of specifically subjective conscious vision.…”
Section: Nibs and Conscious Visionmentioning
confidence: 96%